Double-layer perovskite cathode material and preparation method and application thereof

By reducing the stoichiometric amount of Ba and introducing Ba defects in SOFC cathode material, the PB0.75CC material was prepared by sol-gel method, which solved the problem of reduced cathode ORR activity at traditional SOFC high temperature, achieved the high oxygen reduction catalytic activity and conductivity of the material, and promoted the improvement of SOFC performance.

CN119852431APending Publication Date: 2025-04-18ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510067331.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The excessively high operating temperature of traditional solid oxide fuel cells (SOFCs) leads to a reduced electrocatalytic activity of cathodic oxygen reduction reaction (ORR), affecting the overall battery performance and limiting its commercial application.

Method used

By reducing the stoichiometric amount of Ba at A position, introducing a few Ba defects, and generating more oxygen vacancies, the PrBa0.75Ca0.2Co2O5+δ (PB0.75CC) double-layer perovskite cathode material is prepared by sol-gel method to improve its oxygen reduction catalytic activity and hybrid conductivity.

Benefits of technology

The oxygen reduction catalytic activity and hybrid conductivity of the material are improved, making PB0.75CC an ideal material for SOFC cathodes, showing oxygen reduction activity far higher than that of other cobalt-rich perovskite-type cathode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852431A_ABST
    Figure CN119852431A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid oxide fuel cells, and discloses a double-layer perovskite cathode material and a preparation method and application thereof, the chemical formula of the double-layer perovskite cathode material is PrBa < 0.75 > Ca < 0.2 > Co < 2 > O < 5 + delta >, and delta is oxygen hole concentration, 0.1 lt; delta < lt >; 1. The double-layer perovskite cathode material is prepared by adopting a sol-gel method, the oxygen reduction catalytic activity and the mixed conductivity of the material are improved by controlling stoichiometry of an A-site barium element, introducing a few barium defects and increasing oxygen vacancies by utilizing the A-site defects, and the prepared PB0.75CC can be applied to an SOFC (Solid Oxide Fuel Cell) cathode. The cobalt-rich perovskite cathode material can show oxygen reduction activity far higher than that of other cobalt-rich perovskite cathode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid oxide fuel cells, and more specifically relates to a double-layer perovskite cathode material and a preparation method and application thereof. Background Art

[0002] Solid oxide fuel cell (SOFC) is the most effective device for converting chemical energy into electrical energy. SOFC not only has the advantages of efficient power generation and strong fuel adaptability, but also has the advantages of very low fuel nitrogen oxide and sulfur oxide emissions. However, the high operating temperature of traditional SOFC (>800℃) leads to many problems such as reaction between battery components, long startup time, and high manufacturing cost, which limits its commercialization. At present, lowering the operating temperature of SOFC to the medium temperature range (600-800℃) is the most effective means to solve the problem of SOFC commercial application. However, lowering the operating temperature of SOFC will reduce the electrocatalytic activity of the cathode oxygen reduction reaction (ORR), resulting in an increase in the cathode plan resistance and the electrolyte ohmic resistance. In SOFC, the ORR catalytic activity of the cathode directly affects the performance of the entire SOFC cell, so finding a cathode material with high catalytic activity is one of the research directions to improve the performance of SOFC.

[0003] In recent years, AA'B2O with excellent ionic and electronic mixed conductivity has been 5+δ The double perovskite cathode material has attracted the attention of many researchers. Among them, LnBaCo2O 5+δ (Ln = La, Pr, Nd, Sm, Gd, Y) materials show excellent oxygen reduction catalytic activity and are currently a hot research topic in the field of IT-SOFC cathode materials. However, their electrochemical performance is still insufficient for commercial use. To this end, the present invention reduces the stoichiometry of Ba at the A site, increases oxygen vacancies through appropriate cation deficiency, and improves the oxygen reduction catalytic activity and mixed conductivity of the material. Summary of the invention

[0004] The main purpose of the present invention is to provide a double-layer perovskite cathode material and its preparation method and application in view of the above problems. Its chemical formula is PrBa 0.75 Ca 0.2 Co2O 5+δ (PB0.75CC) is made by the sol-gel method. By reducing the stoichiometry of the A-site element Ba and introducing a small amount of Ba defects, more oxygen vacancies are generated, thereby improving the material's oxygen reduction catalytic activity and mixed conductivity, making PB0.75CC an ideal material for SOFC cathodes.

[0005] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0006] One of the technical solutions of the present invention: a double-layer perovskite cathode material, the chemical formula of the double-layer perovskite cathode material is PrBa 0.75 Ca 0.2 Co2O 5+δ , where δ is the oxygen vacancy concentration, 0.1<δ<1.

[0007] The second technical solution of the present invention: a method for preparing a double-layer perovskite cathode material, comprising the following steps: mixing praseodymium salt, barium salt, calcium salt and cobalt salt according to the stoichiometric ratio in the chemical formula of the double-layer perovskite cathode material and adding water to form a solution, adding a complexing agent solution containing EDTA, citric acid and ammonia water to the solution, and then adjusting the pH to 6-7 to obtain a sol; gelling, drying and calcining the sol in sequence to obtain a double-layer perovskite cathode material.

[0008] More preferably, the praseodymium salt is praseodymium nitrate hexahydrate; the barium salt is barium nitrate; the calcium salt is calcium nitrate trihydrate; and the cobalt salt is cobalt nitrate hexahydrate.

[0009] Further preferably, the ratio of the total molar number of the praseodymium salt, barium salt, calcium salt and cobalt salt to the added amount of water is 19.75mmol:100mL, and the molar ratio of the praseodymium salt, barium salt, calcium salt and cobalt salt is 5:3.75:1:10.

[0010] Further preferably, the molar ratio of the total metal ions in the solution to the ammonium ions in EDTA, citric acid and ammonia water is 1:1-1.5:2-2.5:10-12.

[0011] More preferably, the gelation is carried out by stirring the sol at 80-90° C. for 4-5 hours.

[0012] Further preferably, the drying is performed at 200-250°C for 4-8 hours; and the calcination is performed at 1050-1200°C for 4-6 hours.

[0013] Further preferably, the powder obtained after calcination is mixed with a binder, and the obtained mixture is ground into slurry, and the slurry is dried and calcined to obtain a double-layer perovskite cathode material.

[0014] Further preferably, the binder is terpineol, and the added mass ratio of the powder obtained after calcination to the binder is 3:1-3.

[0015] Technical solution three of the present invention: Application of a double-layer perovskite cathode material in a solid oxide fuel cell.

[0016] Compared with the prior art, the present invention has the following advantages:

[0017] (1) Preparation of PrBa by sol-gel method 0.75 Ca 0.2 Co2O 5+δ (PB0.75CC) perovskite material, citric acid and EDTA are added to the metal solution, and then PB0.75CC is obtained through gelation, drying and calcination;

[0018] (2) PB0.75CC, a low-cobalt titanite cathode material containing A-site defects, introduces a small amount of barium defects by controlling the stoichiometry of the A-site barium element, and utilizes the A-site defects to increase oxygen vacancies, thereby improving the oxygen reduction catalytic activity and mixed conductivity of the material;

[0019] (3) The PB0.75CC of the present invention can be applied to SOFC cathodes and can exhibit an oxygen reduction activity much higher than that of other cobalt-rich perovskite cathode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 These are the X-ray diffraction patterns of the PB0.75CC material prepared in Example 1, the PB0.80CC material prepared in Comparative Example 1, and the PB0.70CC material prepared in Comparative Example 2.

[0021] Figure 2 This is a comparative XRD spectrum of the PB0.75CC material prepared in Example 1 after mixing with GDC.

[0022] Figure 3 This is the conductivity curve of the PB0.75CC material prepared in Example 1.

[0023] Figure 4 Schematic diagram of the impedance curve of the PB0.75CC material prepared in Example 1.

[0024] Figure 5 This is a schematic diagram of the activation energy curve of the PB0.75CC material prepared in Example 1.

[0025] Figure 6 Schematic diagram of the thermogravimetric curve of the PB0.75CC material prepared in Example 1.

[0026] Figure 7 This is a performance test diagram of an O-SOFC single cell using the PB0.75CC material prepared in Example 1 as the cathode material.

[0027] Figure 8 This is a performance test diagram of an O-SOFC single cell using the PB0.80CC material prepared in Comparative Example 1 as the cathode material.

[0028] Fig. 9Schematic diagram of the impedance curve of an O-SOFC single cell using the PB0.75CC material prepared in Example 1 as the cathode material.

[0029] Fig.10 Schematic diagram of the impedance curve of an O-SOFC single cell using the PB0.80CC material prepared in Comparative Example 1 as the cathode material. DETAILED DESCRIPTION

[0030] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.

[0031] Example 1: Preparation of PB0.75CC cathode material

[0032] (1) According to the chemical formula molar ratio of 5:3.75:1:10, 2.1751 g of Pr(NO3)3·6H2O, 0.9800 g of Ba(NO3)2, 0.2362 g of Ca(NO3)2·3H2O, and 2.9103 g of Co(NO3)3·6H2O were weighed and dissolved in 100 mL of deionized water, and stirred until clear to prepare a raw material solution;

[0033] (2) dissolving 5.772 g of ethylenediaminetetraacetic acid (EDTA) and 5.692 g of citric acid in 100 mL of deionized water, adding 23 mL of aqueous ammonia solution, and stirring until the solution is clear to obtain a complex solution; transferring the complex solution to the raw material solution obtained in step (1) by drainage with a glass rod, and then adding an appropriate amount of aqueous ammonia to adjust the solution pH to 7 to obtain a sol;

[0034] (3) The sol was stirred at 80°C for 4 hours, and heated and stirred until a viscous dark purple gel was formed; the gel was further placed in a forced air drying oven and dried at 200°C for 5 hours to obtain a solid precursor; finally, the precursor was calcined in a muffle furnace at 1050°C for 5 hours to obtain the desired PrBa 0.75 Ca 0.2 Co2O 5+δ (PB0.75CC) cathode powder, δ is the oxygen vacancy concentration, 0.1<δ<1, and the Ba element defect at the A site is 0.05.

[0035] Example 2: Preparation of PB0.75CC cathode material

[0036] (1) According to the chemical formula molar ratio of 5:3.75:1:10, 2.1751 g of Pr(NO3)3·6H2O, 0.9800 g of Ba(NO3)2, 0.2362 g of Ca(NO3)2·3H2O, and 2.9103 g of Co(NO3)3·6H2O were weighed and dissolved in 100 mL of deionized water, and stirred until clear to prepare a raw material solution;

[0037] (2) dissolving 8.658 g of ethylenediaminetetraacetic acid (EDTA) and 9.489 g of citric acid in 100 mL of deionized water, adding 34 mL of aqueous ammonia solution, and stirring until the solution is clear to obtain a complex solution; transferring the complex solution to the raw material solution obtained in step (1) by drainage with a glass rod, and then adding an appropriate amount of aqueous ammonia to adjust the solution pH to 7 to obtain a sol;

[0038] (3) The sol was stirred at 80°C for 4 hours, and heated and stirred until a viscous dark purple gel was formed; the gel was further placed in a forced air drying oven and dried at 200°C for 5 hours to obtain a solid precursor; finally, the precursor was calcined in a muffle furnace at 1050°C for 5 hours to obtain the desired PrBa 0.75 Ca 0.2 Co2O 5+δ (PB0.75CC) cathode powder, δ is the oxygen vacancy concentration, 0.1<δ<1, and the Ba element defect at the A site is 0.05.

[0039] Example 3: Preparation of PB0.75CC cathode material

[0040] 1) According to the chemical formula molar ratio of 5:3.75:1:10, 2.1751 g of Pr(NO3)3·6H2O, 0.9800 g of Ba(NO3)2, 0.2362 g of Ca(NO3)2·3H2O, and 2.9103 g of Co(NO3)3·6H2O were weighed and dissolved in 100 mL of deionized water, and stirred until clear to obtain a raw material solution;

[0041] (2) dissolving 5.772 g of ethylenediaminetetraacetic acid (EDTA) and 7.588 g of citric acid in 100 mL of deionized water, adding 23 mL of aqueous ammonia solution, and stirring until the solution is clear to obtain a complex solution; transferring the complex solution to the raw material solution obtained in step (1) by drainage with a glass rod, and then adding an appropriate amount of aqueous ammonia to adjust the solution pH to 6 to obtain a sol;

[0042] (3) The sol was stirred at 90°C for 5 h, heated and stirred until a viscous dark purple gel was formed; the gel was further placed in a forced air drying oven and dried at 200°C for 5 h to obtain a solid precursor; finally, the precursor was calcined in a muffle furnace at 1050°C for 5 h to obtain the desired PrBa 0.75 Ca 0.2 Co2O5+δ (PB0.75CC) cathode powder, δ is the oxygen vacancy concentration, 0.1<δ<1, and the Ba element defect at the A site is 0.05.

[0043] Example 4: Preparation of PB0.75CC cathode material

[0044] 1) According to the chemical formula molar ratio of 5:3.75:1:10, 2.1751 g of Pr(NO3)3·6H2O, 0.9800 g of Ba(NO3)2, 0.2362 g of Ca(NO3)2·3H2O, and 2.9103 g of Co(NO3)3·6H2O were weighed and dissolved in 100 mL of deionized water, and stirred until clear to obtain a raw material solution;

[0045] (2) dissolving 5.772 g of ethylenediaminetetraacetic acid (EDTA) and 7.588 g of citric acid in 100 mL of deionized water, adding 23 mL of aqueous ammonia solution, and stirring until the solution is clear to obtain a complex solution; transferring the complex solution to the raw material solution obtained in step (1) by drainage with a glass rod, and then adding an appropriate amount of aqueous ammonia to adjust the solution pH to 7 to obtain a sol;

[0046] (3) The sol was stirred at 80°C for 4 hours, and heated and stirred until a viscous dark purple gel was formed; the gel was further placed in a forced air drying oven and dried at 200°C for 5 hours to obtain a solid precursor; finally, the precursor was calcined in a muffle furnace at 1050°C for 5 hours to obtain the desired PrBa 0.75 Ca 0.2 Co2O 5+δ (PB0.75CC) cathode powder, δ is the oxygen vacancy concentration, 0.1<δ<1, and the Ba element defect at the A site is 0.05.

[0047] Example 5: Preparation of PB0.75CC cathode material

[0048] 1) According to the chemical formula molar ratio of 5:3.75:1:10, 2.1751 g of Pr(NO3)3·6H2O, 0.9800 g of Ba(NO3)2, 0.2362 g of Ca(NO3)2·3H2O, and 2.9103 g of Co(NO3)3·6H2O were weighed and dissolved in 100 mL of deionized water, and stirred until clear to obtain a raw material solution;

[0049] (2) dissolving 5.772 g of ethylenediaminetetraacetic acid (EDTA) and 7.588 g of citric acid in 100 mL of deionized water, adding 23 mL of aqueous ammonia solution, and stirring until the solution is clear to obtain a complex solution; transferring the complex solution to the raw material solution obtained in step (1) by drainage with a glass rod, and then adding an appropriate amount of aqueous ammonia to adjust the solution pH to 7 to obtain a sol;

[0050] (3) The sol was stirred at 80°C for 4 hours, and heated and stirred until a viscous dark purple gel was formed; the gel was further placed in a forced air drying oven and dried at 250°C for 8 hours to obtain a solid precursor; finally, the precursor was calcined in a muffle furnace at 1200°C for 6 hours to obtain the desired PrBa 0.75 Ca 0.2 Co2O 5+δ (PB0.75CC) cathode powder, δ is the oxygen vacancy concentration, 0.1<δ<1, and the Ba element defect at the A site is 0.05.

[0051] Comparative Example 1: Preparation of PB0.80CC cathode material. The preparation is similar to that of Example 1, except that the stoichiometric ratio of the barium salt is different.

[0052] (1) According to the chemical formula, 2.1751 g of Pr(NO3)3·6H2O, 1.0453 g of Ba(NO3)2, 0.2362 g of Ca(NO3)2·3H2O, and 2.9103 g of Co(NO3)3·6H2O were weighed and dissolved in 100 mL of deionized water, and stirred until clear to prepare a raw material solution;

[0053] (2) dissolving 5.8448 g of ethylenediaminetetraacetic acid (EDTA) and 7.588 g of citric acid in 100 mL of deionized water, adding 23 mL of aqueous ammonia solution, and stirring until the solution is clear to obtain a complex solution; transferring the complex solution to the raw material solution obtained in step (1) by drainage with a glass rod, and then adding an appropriate amount of aqueous ammonia to adjust the solution pH to 7 to obtain a sol;

[0054] (3) The sol was stirred at 80°C for 4 hours, and heated and stirred until a viscous dark purple gel was formed; the gel was further placed in a forced air drying oven and dried at 200°C for 5 hours to obtain a solid precursor; finally, the precursor was calcined in a muffle furnace at 1050°C for 5 hours to obtain the desired PrBa 0.8 Ca 0.2 Co2O 5+δ (PB0.80CC) cathode powder, δ is the oxygen vacancy concentration, 0.1<δ<1.

[0055] Comparative Example 2: Preparation of PB0.70CC cathode material. The preparation is similar to that of Example 1, except that the stoichiometric ratio of the barium salt is different.

[0056] (1) According to the chemical formula molar ratio of 5:3.5:1:10, 2.1751 g of Pr(NO3)3·6H2O, 0.9147 g of Ba(NO3)2, 0.2362 g of Ca(NO3)2·3H2O, and 2.9103 g of Co(NO3)3·6H2O were weighed and dissolved in 100 mL of deionized water, and stirred until clear to prepare a raw material solution;

[0057] (2) dissolving 5.6987 g of ethylenediaminetetraacetic acid (EDTA) and 5.6195 g of citric acid in 100 mL of deionized water, adding 23 mL of aqueous ammonia solution, and stirring until the solution is clear to obtain a complex solution; transferring the complex solution to the raw material solution obtained in step (1) by drainage with a glass rod, and then adding an appropriate amount of aqueous ammonia solution to adjust the solution pH to 7 to obtain a sol;

[0058] (3) The sol was stirred at 80°C for 4 hours, and heated and stirred until a viscous dark purple gel was formed; the gel was further placed in a forced air drying oven and dried at 200°C for 5 hours to obtain a solid precursor; finally, the precursor was calcined in a muffle furnace at 1050°C for 5 hours to obtain the desired PrBa 0.70 Ca 0.2 Co2O 5+δ (PB0.70CC) cathode powder, δ is the oxygen vacancy concentration, 0.1<δ<1, and the Ba element defect at the A site is 0.10.

[0059] Application example 1: Single cell preparation

[0060] The PB0.75CC cathode powder of Example 1 and the PB0.80CC cathode powder of Comparative Example 1 were respectively mixed with pineneol in a mass ratio of 3:2, and then ground into an agate mortar to prepare cathode slurry, which was then screen-printed onto an anode-supported single cell and calcined at 1000°C for 2h to obtain a porous cathode layer. The prepared anode-supported single cell O-SOFC had a configuration of NiO-YSZ|YSZ|GDC|PBCC, with anode NiO-YSZ as a support, electrolyte YSZ as an oxygen ion conductor, and cathode layer being PB0.75CC or PB0.80CC.

[0061] Performance characterization of single-cell O-SOFC: The prepared single-cell sheet was sealed onto a quartz tube with silver glue, assembled into a test mold and placed in a tube furnace for electrochemical performance testing. The test temperatures of the battery were 650°C, 700°C, 750°C, and 800°C, respectively. Air atmosphere was introduced into the cathode side, and hydrogen was introduced into the anode side as fuel. The hydrogen flow rate was controlled by a flow controller to 50mL / min. The current density-voltage (IV) and current density-power density (IP) curves of the battery were measured by a Garmyinterface 5000E electrochemical workstation.

[0062] like Figure 1 and Figure 2As shown, PB0.75CC and PB0.80CC maintain a double perovskite structure, while the double perovskite structure of PB0.70CC becomes a single perovskite structure, and the structure is destroyed. No impurities are generated in the XRD spectrum, and the characteristic diffraction peaks of GDC are not offset or disappeared. All diffraction peaks are diffraction peaks of the cathode material sample and the electrolyte, indicating that the prepared cathode material sample does not react with the GDC electrolyte. The PB0.75CC cathode material of the present invention has good chemical compatibility with GDC, which meets the requirements for the selection of chemical compatibility of SOFC cathode materials.

[0063] like Figure 3 The conductivity curves of PB0.75CC of Example 1 and PB0.80CC of Comparative Example 1 at 300°C to 800°C in air atmosphere are shown. It can be seen that the conductivity first increases with temperature and then decreases continuously, which is a transition from semiconductor to metal conduction behavior. Since PB0.75CC has more oxygen vacancies as electron holes, it has higher conductivity.

[0064] like Figure 4 As shown, the polarization impedance (ASR) of the series of cathode materials was tested using a symmetrical battery method. The PB0.75CC sample of Example 1 of the present invention was tested for ASR under air atmosphere, 650°C and 800°C, and an EIS impedance curve was obtained. It can be seen that the ASR of the sample shows a gradually decreasing trend with increasing temperature, indicating that the redox ability of the cathode material sample is enhanced with increasing temperature. This is mainly because the increase in temperature is beneficial to the increase in charge migration rate and chemical reaction rate, thereby resulting in a decrease in the ASR of the cathode material.

[0065] like Figure 5 The activation energy curves obtained by EIS fitting are shown for the PB0.75CC material prepared in Example 1 and the PB0.80CC prepared in Comparative Example 1. The activation energy of PB0.75CC is 1.98 eV, which is lower than that of PB0.80CC, indicating that it has a lower reaction energy barrier, making the oxygen reduction reaction easier to proceed.

[0066] like Figure 6 The thermogravimetric curve of the PB0.75CC material prepared in Example 1 from room temperature to 800°C in a nitrogen atmosphere is shown. Figure 6 It can be seen that the weight loss of PB0.75CC is 1.376%. This is because at high temperature, cobalt ions are reduced, resulting in more lattice oxygen release and more oxygen vacancies.

[0067] like Figure 7The sample PB0.75CC of Example 1 is used as the cathode material of a single cell to prepare a single cell NiO-YSZ|YSZ|GDC|PB0.75CC. Figure 8 Compared with the IVP curve of the PB0.80CC material prepared in Comparative Example 1, it can be seen that the discharge power density of the sample PB0.75CC of Example 1 is higher. The output power density of the single cell at 800°C is as high as 929mW / cm 2 , indicating that PB0.75CC is an excellent O-SOFC cathode material, and the O-SOFC based on PB0.75CC has high oxygen reduction activity under high temperature working conditions.

[0068] like Fig. 9 The EIS impedance spectrum of the single cell NiO-YSZ|YSZ|GDC|PB0.75CC prepared in Example 1 is shown as the cathode material of the single cell. It can be found that at 800°C, its ASR is only 0.6Ω·cm 2 ,like Fig.10 As shown, PB0.80CC prepared in Comparative Example 1 is used as a single cell cathode material, and its polarization impedance is larger, indicating that the ORR activity of PB0.75CC prepared in Example 1 is better.

[0069] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0070] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A double-layer perovskite cathode material, characterized in that: The chemical formula of the double-layer perovskite cathode material is PrBa 0.75 Ca 0.2 Co2O 5+δ , where δ is the oxygen vacancy concentration, 0.1<δ<1.

2. A method for preparing the double-layer perovskite cathode material as claimed in claim 1, characterized in that: The method comprises the following steps: mixing praseodymium salt, barium salt, calcium salt and cobalt salt according to the stoichiometric ratio in the chemical formula of the double-layer perovskite cathode material and adding water to prepare a solution; adding a complexing agent solution containing EDTA and citric acid to the solution; and then adding ammonia water to adjust the pH to 6-7 to prepare a sol; and sequentially subjecting the sol to gelation, drying and calcination to prepare the double-layer perovskite cathode material.

3. The method for preparing a double-layer perovskite cathode material according to claim 2, characterized in that: The praseodymium salt is praseodymium nitrate hexahydrate; the barium salt is barium nitrate; the calcium salt is calcium nitrate trihydrate; and the cobalt salt is cobalt nitrate hexahydrate.

4. The method for preparing a double-layer perovskite cathode material according to claim 2 or 3, characterized in that: The ratio of the total molar number of the praseodymium salt, barium salt, calcium salt and cobalt salt to the added amount of water is 19.75mmol:100mL, and the molar ratio of the praseodymium salt, barium salt, calcium salt and cobalt salt is 5:3.75:1:

10.

5. The method for preparing the double-layer perovskite cathode material according to claim 2, characterized in that: The molar ratio of the total metal ions in the solution to the ammonium ions in EDTA, citric acid and ammonia water is 1:1-1.5:2-2.5:10-12.

6. The method for preparing a double-layer perovskite cathode material according to claim 2, characterized in that: The gelation is carried out by stirring the sol at 80-90° C. for 4-5 hours.

7. The method for preparing the double-layer perovskite cathode material according to claim 2, 5 or 6, characterized in that: The drying is performed at 200-250° C. for 4-8 hours; and the calcination is performed at 1050-1200° C. for 4-6 hours.

8. The method for preparing a double-layer perovskite cathode material according to claim 2, 5 or 6, characterized in that: The powder obtained after calcination is mixed with a binder, and the obtained mixture is ground into slurry. The slurry is dried and calcined to obtain a double-layer perovskite cathode material.

9. The method for preparing a double-layer perovskite cathode material according to claim 8, characterized in that: The binder is terpineol, and the added mass ratio of the powder obtained after calcination to the binder is 3:1-3.

10. Use of the double-layer perovskite cathode material according to any one of claims 1 to 9 in a solid oxide fuel cell.